RNA-Seq, physiological, and biochemical analysis of burley tobacco response to nitrogen deficiency - Yafei Li (Nature Portfolio, 2021)
Abstract To explore the effects of nitrogen deficiency in burley tobacco, two varieties were cultivated and subjected to conditions of sufficient and deficient nitrogen. The natural characteristics of varieties TN90 and TN86 during tobacco cultivation were similar for nitrogen metabolism. Both carbon and nitrogen metabolism were significantly affected by reducing amounts of applied nitrogen. Under nitrogen-deficient conditions, average leaf biomass, root weight, photosynthetic rate (Pn), pigment levels, total nitrogen, and nitrate content of TN86 and TN90 were significantly decreased by 52.88%, 69.19%, 22.65%, 46.80%, 37.42%, and 79.15%, respectively (p < 0.01). Nicotine and soluble reducing sugar contents were significantly decreased by 96.67% and 95.12%, respectively, in TN86 roots (p < 0.01), which was consistent with the reductions in root surf area, average diameter, and root volume. Nitrogen deficiency induced 6318 differentially expressed genes in both TN90 and TN86, which were highly expressed. In total, 428 upregulated genes were analysed and found to be mainly enriched in the MAPK signalling pathway, sesquiterpenoid and triterpenoid biosynthesis, and arginine and proline metabolism. Meanwhile, 213 downregulated genes were analysed and found to be mainly enriched in photosynthesis, nitrogen metabolism, and amino acid biosynthesis. Reduced pigment content and Pn may result in low carbohydrate formation and decreased leaf biomass in burley tobacco under nitrogen-deficient conditions.